Pengaruh konsep kendiri, personaliti dan prestasi akademik terhadap pembentukan kemahiran generik dalam kalangan bakal guru di Universiti Awam Malaysia - Nurull Salmi, Md. Dazali (2018)
Quality human capital development depends largely on the characteristics of educators. Having a multiple of skills such as generic skills is an essential requirement for every individual and it is a frequent issue being discussed. The purpose of this study is to survey the level of self-concept, academic performance, and generic skills of teachers, identify gender-based difference in generic skills, and analyse all variables in testing the generic skills model. This study involved 377 final-year students taking Bachelor of Education from various public learning institutions as samples and tested using the Junior Eysenck Personality Inventory (JEPI), Tennessee Self Concept Scale, and the Malaysian Generic Skills Instrument (MyGSI) questionnaires for data collection. Results were analysed using T-test, Correlation test, and Structural Equation Modelling (SEM). The results of the analysis showed that the level of self-concept, academic performance and generic skills of students was at a high level. The T-test conducted had shown that there was no significant difference between the levels of generic skills according to gender. The study had also indicated that there was a significant relationship between self-concept and generic skills. Hence, the stakeholders should pay attention to the self-concept elements in developing the generic skills of the students especially among the pre-service teachers. This is important in preparing teachers to master pedagogy because their role is essential in determining the quality of education at the school level and graduates for the long term.